Fast synthesis of TiNi by mechanical alloying and its hydrogenation properties - Nobuki, Tohru; Crivello, Jean-Claude; Cuevas, Fermin; Joubert, Jean-Marc (International Journal of Hydrogen Energy, 2019)
Mechanical alloying is widely used for the synthesis of hydrogen storage materials. However, amorphization and contamination triggered by long-time milling are serious drawbacks for obtaining efficient hydrogen storage. In this work, short-time ball milling synthesis is explored for a representative hydride forming compound: TiNi. Through structural, morphological and chemical characterizations, we evidence that formation of TiNi is complete in only 20 min with minor Fe contamination (0.2 wt%). Cross-sectional analysis of powder stuck on milling balls reveals that alloy formation occurs through the interdiffusion between thin layers of co-laminated pure elements. Hydrogenation thermodynamics and kinetics of short-time mechanically alloyed TiNi are similar to those of coarse-grained compounds obtained by classical high-temperature melting. Mechanical alloying is a suitable method for fast and energy-efficient synthesis of intermetallic compounds such as TiNi. •TiNi phase synthesized in only 20 min of mechanical alloying.•TiNi formation mechanism visualized by scanning electron microscopy.•Mechanically alloyed TiNi has a high hydrogen capacity and fast absorption kinetics.•Mechanical alloying is an energy-efficient method for TiNi synthesis.